Le mineur délinquant face au service public pénitentiaire - Beddiar, Nadia (Université Lille 2, 2011)
L'administration pénitentiaire française connaît, depuis plusieurs années, d'importantes mutations vis-à-vis de ses missions, qui tendent vers une externalisation et de son personnel. L’amélioration de la réinsertion des détenus est devenue un impératif majeur, surtout en ce qui concerne les mineurs incarcérés, en vue de réduire les risques de récidive. Il s'agit d'expliquer et de qualifier ces changements correspondants à un besoins d'adaptation de cette administration envers l'évolution de la population carcérale, tout en améliorant ses relations avec les autres organismes publics (le ministère de l'éducation nationale notamment) afin de confirmer la politique de décloisonnement et de partenariat, suivie par l'administration pénitentiaire. Cette étude tentera également de dresser un premier bilan concernant les efforts fournis par cette administration publique dans le cadre particulier des établissements pénitentiaires pour mineurs. The correctional institution is experiencing a profound process of modernization under the influence of European and constitutional law, which tends to assign to it all the characteristics of a public service and significantly adds to the law of enforcement of sentences. This normative development, under the control of an administrative judge, has introduced the basis of a genuine legal status for minors as coerced users of this public service. Efforts carried out by the penitentiary administration in the aim of establishing detention rules that apply and are adjusted to the different categories of prison population, and particularly to minors, are changing the traditional/classic conception of the prison’s missions. The specificity of detention rules, as confirmed by the creation of detention facilities for minors and the search for a legal status for the minor inmate, is endorsed by the opening up of the penitentiary administration and the building of partnerships with other institutional actors. The mobilization of new resources constitutes a fundamental axe in the preparation of the social rehabilitation of minors, in their own best interest and benefit. The issues around the correctional framing in the objective to define the administrative status of the minor inmate lead to double angled analysis: the fixing of the foundations of prison law applicable to minors, and the application of this law which illustrates the need for an adaptation of the penitentiary action when it comes to minors.